DINAMIKA KONSENTRASI PASAR INDUSTRI PERTELEVISIAN NASIONAL - Bestian Nainggolan (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2018)
The weakening macro condition of Indonesia’s economy in the last five years has influenced the economic performance of the television media industry. Since that time, media advertising expenditure as the largest revenue source for the television industry has been declining. The purpose of this research is to know how each group of broadcast media corporations in this country are competing and trying to control the market of the media industry. Methods used in this research was adopting both the quantitative analysis which leans back upon the organization the field of industrial (in theory). Relying on the Structure-Conduct-Performance analysis model, the result of this research reveals that although the economic slowdown impacts the economic performance of the corporate group of television, the roles of three groups of television media corporations: Global Mediacom, Elang Mahkota Teknologi, and Visi Media Asia remain dominant. The market audience and television ads are concentrated in these three groups and build an increasingly uncompetitive structure for other industry players. This research contributes to give insight on the current economic situation of national television industry.